Analysis Of The Implementation Of Tax Amnesty In Indonesia In 2016-2017 - wartoyo wartoyo; usman usman (Journal of Islamic Economy and Business (JIsEB), 2024)
The purpose of this research is to analyze the implementation of the tax amnesty policy in Indonesia by describing the indicators of its success on macroeconomic variables. This research uses a descriptive qualitative approach using the type of case study research method with data analysis techniques using literature study. Based on the research results that the tax amnesty program in Indonesia based on Law Noumber 11 of 2016 has not been successful in increasing taxpayer compliance, and the realization of tax amnesty revenue is still low from the predetermined target. However, in its implementation, it has a positive effect on the Indonesian economy such as increasing liquidity, improving the rupiah exchange rate, lowering interest rates and increasing investment